Resistivity of Graphite Intercalation Compounds with Bromine and Aluminum Chloride under the Pressure - I.V. Ovsienko; T.A. Len; L.Yu. Matzui; O.V. Zhuravkov; O.I. Prokopov; Yu.A. Kunitskyi (Журнал нано- та електронної фізики)
The paper presents the results of investigation of resistivity of acceptor graphite intercalation compounds in the temperature region of phase transition in the intercalate layers. The features of phase transitions in intercalate layers under pressure and temperature are found. It is shown that the resistivity of graphite intercalation compounds increases under pressure, the temperature of phase transformations in the intercalate layer shifts to higher temperatures. Parameters of the electronic structure of graphite intercalation compounds and their pressure dependence are estimated. Changes in the resistivity of graphite intercalation compounds under pressure are calculated.